1997
DOI: 10.1002/jlb.61.5.609
|View full text |Cite
|
Sign up to set email alerts
|

Leukosialin (CD43) behavior during adhesion of human monocytic THP-1 cells to red blood cells

Abstract: To understand the modulation and the behavior of glycocalyx elements during adhesion, we explored one of its components, the CD43 molecule, on human monocytic THP-1 cells exposed to cytokine stimulation and its redistribution during heterotypic adhesion to opsonized erythrocytes. First we demonstrated by immunofluorescence and immunoprecipitation that CD43 is dys-sialylated in monocytic THP-1 cells stimulated by interferon-gamma (IFN-gamma) and tumor necrosis factor alpha (TNF-alpha) and stimulation increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 49 publications
3
22
0
Order By: Relevance
“…Since the 7 patients studied with a drastic decrease in the expression of CD43 sialylo-dependent epitope did not exhibit a decrease of MFI with the L10 mAb, we suggest that the modification was more a dys-sialylation rather than a diminished number of CD43 molecules. Similar results were obtained in a previous work on neuraminidase-treated cells [9]. In some cases, we observed two subpopulations of monocytes with differential expression of CD43 and such features were observed in the rat [15, 16].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Since the 7 patients studied with a drastic decrease in the expression of CD43 sialylo-dependent epitope did not exhibit a decrease of MFI with the L10 mAb, we suggest that the modification was more a dys-sialylation rather than a diminished number of CD43 molecules. Similar results were obtained in a previous work on neuraminidase-treated cells [9]. In some cases, we observed two subpopulations of monocytes with differential expression of CD43 and such features were observed in the rat [15, 16].…”
Section: Discussionsupporting
confidence: 80%
“…Adhesive and antiadhesive properties have been attributed to CD43 [5, 6]. CD43 has been demonstrated to be redistributed during adhesion, both on lymphocytes [7, 8]and on monocytes [9]. Moreover, we have demonstrated that on cultured human monocytes exposed to IFN-γ and TNF-α stimulation, CD43 is partially dys-sialylated [9].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Changes in the glycosylation pattern of its extracellular domain allow CD43 to function as a proadhesive counter receptor for galectin-1, ICAM-1, E-selectin, sialoadhesin and MHC Class I molecules. 16,23,[25][26][27][28]37,39,40 While CD43 is normally restricted in its expression to leukocytes and platelets, aberrant expression has been consistently described in colon and salivary gland cancers. [41][42][43][44] In addition, limited analysis suggested that NSCLC but not SCLC might also be characterized by CD43 expression.…”
Section: Discussionmentioning
confidence: 99%
“…12,41,43 Exclusions of CD43 from the leading edge of polarized cells and from attachment sites further suggest possible function of CD43 in cell rounding. [11][12][13][14] Meanwhile, several adhesion molecules are localized, if not enriched, in leukocyte microvilli. 22,24,25,29 We also observed localization of α4β1 integrin in microvilli in CD43-HEK293T cells.…”
Section: Methodsmentioning
confidence: 99%